2022
DOI: 10.1007/s00262-022-03166-9
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and soluble immune checkpoint signaling forms PD-L1 and PD-1 in renal tumor tissue and in blood

Abstract: Immune checkpoint blockade therapy is a treatment option of various metastatic cancer diseases including renal cell carcinoma (RCC). Approved antibody drugs target the co-inhibitory signaling of Programmed Cell Death Ligand-1 (PD-L1) and its receptor Programmed Cell Death-1 (PD-1). The combined evaluation of PD-L1 and PD-1 at the mRNA and protein levels in tumor tissue with differentiation of tumor and immune cells as well as of soluble forms (sPD-L1) and (sPD-1) in blood is of basic interest in assessing biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…reported that PD‐L1 expression was higher in immune cells infiltrating ovarian cancer tissue compared with tumor cells, and that sPD‐L1 correlated with PD‐L1 expression in immune cells in the blood. Keber et al 28 . also found that sPD‐L1 in the blood increased following resection of renal cancer, and that sPD‐L1 levels correlated with PD‐L1 mRNA expression in the blood.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…reported that PD‐L1 expression was higher in immune cells infiltrating ovarian cancer tissue compared with tumor cells, and that sPD‐L1 correlated with PD‐L1 expression in immune cells in the blood. Keber et al 28 . also found that sPD‐L1 in the blood increased following resection of renal cancer, and that sPD‐L1 levels correlated with PD‐L1 mRNA expression in the blood.…”
Section: Discussionmentioning
confidence: 90%
“…26 Okła et al 27 reported that PD-L1 expression was higher in immune cells infiltrating ovarian cancer tissue compared with tumor cells, and that sPD-L1 correlated with PD-L1 expression in immune cells in the blood. Keber et al 28 also found that sPD-L1 in the blood increased following resection of renal cancer, and that sPD-L1 levels correlated with PD-L1 mRNA expression in the blood. Since inflammatory cytokines, such as interferon gamma (IFNγ), IFNα, and tumor necrosis factor alpha (TNFα), increase secretion of PD-L1, 21 our study indicates that sPD-L1 levels may also reflect the potential activation of tumor immunity in patients with a low tumor burden, resulting in a prognosis benefit through anti-PD-1 treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous studies (n = 22, involving 1,223 patients) have reported on the effect of conventional therapies, including chemotherapy, targeted drug therapy, radiotherapy, surgery, or combinations of these modalities, on the level of sPD-L1 (Table S4). The majority of these studies have found that sPD-L1 is increased in patients upon treatment [62,65,67,71,89,232,233,237,[239][240][241][242][243]; however, others have reported that levels either remained constant [51,62,64,68,81,89,222,243] or decreased [55,223,227,244] following treatment with conventional therapies. Many fewer studies (n = 8, involving 513 patients) have reported on the association between patient outcomes and levels or changes in the levels of sPD-L1 following treatment with conventional therapies (Table 5).…”
Section: Spd-l1mentioning
confidence: 99%
“…Multiple studies (n = 13, involving 641 patients) have also reported on the effects of conventional therapies on the level of sPD-1, with some reporting an increase [65,68,237,240,246], no change [64,67,222,239,241,243] or a decrease [242,245] after therapy (Table S5). Only four studies, involving 187 patients, have evaluated the association between levels or changes in the levels of sPD-1 after conventional therapy and patient outcome (Table S6).…”
Section: Spd-1mentioning
confidence: 99%
“…High levels of soluble PD1/PDL1 and lymphocyte-activation gene 3 (LAG-3) were detected in basal cell carcinoma patients, which may serve as prognostic/predictive biomarkers [ 8 ]. Also, which related to immune balance, the researchers found that sPD1 and sPDL1 were elevated in gastric carcinoma and renal cell carcinoma, they can also be considered to be an early marker of deterioration [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%